Food, nutrition, and population health: exploring the role of food as preventive medicine - Zigmont, Victoria A.; Causey, Traci (2019)
Keywords: dept.pch

The impact of caloric information on college student's fast food purchasing intentions - Zigmont, Victoria A; Bulmer, Sandra Minor (American journal of health education, 2015)
Background: Fast food establishments are available on many college campuses and, as a result, many students consume foods that are high in calories and contribute to unhealthy weight gain. Purpose: This study measured college students' knowledge of the calorie content for fast food items and whether the provision of calorie information for those foods influenced their future purchasing intentions. Method: Randomly selected undergraduate college students (N = 201) completed an online survey that measured baseline knowledge of calorie content for a fast food item and intention to purchase that item in the future. After provision of accurate calorie information, students were posttested for intention to purchase that item in the future. Results: The majority of students underestimated calorie content for fast food items. After receiving accurate calorie information, those who initially underestimated calorie content were significantly more likely to change their intention to purchase that food item in the future. Discussion: Many college students are interested in avoiding high-calorie fast food items but are uninformed about calorie content. Translation to Health Education Practice: Colleges should provide calorie information for fast food items at the point of purchase so that students can make informed decisions that will promote their health. © 2015, Copyright © SHAPE America.
Keywords: dept.hhs; dept.pch

Understanding the why of college student food insecurity - Zigmont, Victoria A.; Linsmeier, Abigail M.; Gallup, Peggy (Journal of Hunger & Environmental Nutrition, 2019)
This study sought to understand why college students are food insecure and what the impact is on their academics. A generic qualitative study design was utilized that consisted of written surveys and semi-structured interviews. Participants (n = 19) self-identified as food insecure based upon their answers to the 6-item Short Form Food Security Survey Module. Two researchers independently coded the data for themes and patterns. Risk factors for food insecurity included finances, time, and lack of resources/skills to provide for healthy eating. Time and money put commuter students at risk for food insecurity. While students within this convenience sample reported negative impacts on their academic achievement from food insecurity, their coping mechanisms prioritized cost and convenience over food quality, possibly exacerbating their situation.College food insecurity is a complex issue and raw measurements may not paint a complete picture. Conflicting priorities in addition to income and time pressures mean that interventions should be tailored from current approaches. Colleges may need to find unique ways to ensure food security for at risk students within financial aid packages and/or university programs to ensure student success.
Keywords: College students; dept.pch; food insecurity; higher education; hunger; peer-reviewed; university students

Examining Delivery Method and Infant Feeding Intentions between Women in Traditional and Non-Traditional Prenatal Care. - Risisky, Deb; Chan, Ronna L; Zigmont, Victoria A; Asghar, Syed Masood; DeGennaro, Nancy (Maternal and child health journal, 2018)
Introduction The purpose of the study is to evaluate delivery method and breastfeeding initiation in women enrolled in group prenatal care (CenteringPregnancy) and in traditional prenatal care. Methods Data were obtained from medical records of a hospital-based midwifery practice in south central Connecticut that offered both types of prenatal care programs. Medical information from 307 women enrolled in this practice was included in the analysis. Out of the 307, 80 were enrolled in group prenatal care. Socio-demographic, lifestyle, and previous and current obstetrical information from medical records formed the basis of comparison. Bivariate and logistic regression analyses were carried out. Results Women in Centering had fewer planned cesarean sections (1.3 vs. 12.8%) and had a higher breastfeeding initiation (88.7 vs. 80.0%). However, Centering women were found to have a higher portion of unplanned cesarean sections (27.5 vs. 11.0%). Both the unadjusted and the adjusted odds ratios of having a cesarean planned delivery were lower in the group care. Women in Centering had 2.44 (95% CI 1.05, 5.66) times the odds of breastfeeding initiation compared to the odds for women in traditional prenatal care after adjusting for maternal age, smoking status, gestation and race. Discussion CenteringPregnancy can have positive impact for the woman and baby. This program implementation saw lower rates of elective cesarean sections and increased breastfeeding compared to women in traditional care.
Keywords: *Breast Feeding/px [Psychology]; *Breast Feeding/sn [Statistics & Numerical Data]; *Cesarean Section/sn [Statistics & Numerical Data]; *Intention; *Mothers; *Prenatal Care/mt [Methods]; Adult; Breast Feeding; Breastfeeding; CenteringPregnancy; Cesarean Section; Cesarean section; Connecticut; Female; Group Processes; Humans; Infant; Infant, Newborn; Intention; Mothers; Mothers/px [Psychology]; Mothers/sn [Statistics & Numerical Data]; Pregnancy; Prenatal Care; Prenatal care; Standard of Care; adult; behavior; breast feeding; cesarean section; comparative study; dept.pch; female; group process; health care quality; human; infant; mother; newborn; peer-reviewed; pregnancy; prenatal care; procedures; psychology; statistics and numerical data

An Evaluation of Reach for a Work Site Implementation of the National Diabetes Prevention Program Focusing on Diet and Exercise. - Zigmont, Victoria A; Shoben, Abigail B; Kaye, Gail L; Snow, Richard J; Clinton, Steven K; Harris, Randall E; Olivo-Marston, Susan E (American journal of health promotion : AJHP, 2018)
PURPOSE: Our objective is to evaluate the "reach" component of the Reach Effectiveness Adoption Implementation Maintenance (RE-AIM) framework by comparing prediabetics who were and were not interested in enrolling in a free work site diabetes prevention program (DPP) during the first year of the program. Reach is defined as the proportion of eligible participants who enroll in a health program., DESIGN: A cross-sectional study design was used., SETTING: The setting was a large health system in the Midwest., PARTICIPANTS: Prediabetic health plan enrollees and spouses (N = 2158)., MEASURES: An online health survey, annual voluntary biometric screenings delivered by a trained health-care professional using standardized protocols via point-of-care testing, and records from the DPP office were the sources of data for this study., ANALYSIS: Health behaviors and biometric screening results were simultaneously compared using multivariable logistic regression., RESULTS: The study population was 63% female, 79% white, and 16% black, and the mean age was 50.2 years (SD = 10.2). The reach of this program was 10%. Prediabetics were more likely to express interest in the DPP, if they were female (adjusted odds ratio [AOR]: 2.4; 95% confidence interval [95% CI]: 1.55-3.72; P < .001), black (AOR = 2.23; 95% CI: 1.43-3.47; P < .001), older in age (AOR: 1.08; 95% CI: 0.99-1.17; P = .05), or had a high-risk waist circumference (AOR = 1.44; 95% CI: 0.98-2.13; P = .07), lower self-efficacy to make healthy changes (AOR = 0.48; 95% CI: 0.26-0.91; P = .03), and 5 or more doctor visits in the last year (AOR = 2.13; 95% CI: 0.99-4.57; P = .05), after controlling for other covariates., CONCLUSION: Current recruitment and implementation strategies are reaching only a small group of individuals who are not representative of the larger prediabetic population. These findings inform future engagement strategies, and we recommend that public health practitioners evaluate reach to ensure that health promotion programs are of high value.
Keywords: *Diabetes Mellitus, Type 2/pc [Prevention & Control]; *Diet/px [Psychology]; *Exercise/px [Psychology]; *Health Promotion/mt [Methods]; *Healthy Lifestyle; *Occupational Health; *Workplace/px [Psychology]; Adult; Cross-Sectional Studies; Diabetes Mellitus, Type 2; Diet; Exercise; Female; Health Promotion; Healthy Lifestyle; Humans; Male; Middle Aged; Midwestern United States; Occupational Health; Program Evaluation; RE-AIM framework; United States; Workplace; adult; cross-sectional study; dept.pch; diabetes prevention program; diet; evaluation study; exercise; female; health promotion; healthy lifestyle; human; male; middle aged; non insulin dependent diabetes mellitus; occupational health; peer-reviewed; prediabetes; procedures; program evaluation; psychology; work site health promotion; workplace

Statin users have an elevated risk of dysglycemia and new‐onset‐diabetes - Zigmont, Victoria A.; Shoben, Abigail B.; Lu, Bo; Kaye, Gail L.; Clinton, Steven K.; Harris, Randall E.; Olivo‐Marston, Susan E. (Diabetes/Metabolism Research and Reviews, 2019)
Keywords: dept.pch; dysglycemia; inverse probability weighting; peer-reviewed; statin use; survival analysis; type 2 diabetes mellitus

Associations between prediagnostic blood glucose levels, diabetes, and glioma. - Schwartzbaum, Judith; Edlinger, Michael; Zigmont, Victoria; Stattin, Par; Rempala, Grzegorz A; Nagel, Gabriele; Hammar, Niklas; Ulmer, Hanno; Foger, Bernhard; Walldius, Goran; Manjer, Jonas; Malmstrom, Hakan; et al. (Scientific Reports, 2017)
Previous literature indicates that pre-diagnostic diabetes and blood glucose levels are inversely related to glioma risk. To replicate these findings and determine whether they could be attributed to excess glucose consumption by the preclinical tumour, we used data from the Apolipoprotein MOrtality RISk (AMORIS) (n = 528,580) and the Metabolic syndrome and Cancer project (Me-Can) cohorts (n = 269,365). We identified individuals who were followed for a maximum of 15 years after their first blood glucose test until glioma diagnosis, death, emigration or the end of follow-up. Hazard ratios (HRs), 95% confidence intervals (CIs) and their interactions with time were estimated using Cox time-dependent regression. As expected, pre-diagnostic blood glucose levels were inversely related to glioma risk (AMORIS, P trend = 0.002; Me-Can, P trend = 0.04) and pre-diagnostic diabetes (AMORIS, HR = 0.30, 95% CI 0.17 to 0.53). During the year before diagnosis, blood glucose was inversely associated with glioma in the AMORIS (HR = 0.78, 95% CI 0.66 to 0.93) but not the Me-Can cohort (HR = 0.99, 95% CI 0.63 to 1.56). This AMORIS result is consistent with our hypothesis that excess glucose consumption by the preclinical tumour accounts for the inverse association between blood glucose and glioma. We discuss additional hypothetical mechanisms that may explain our paradoxical findings.
Keywords: *Blood Glucose/me [Metabolism]; *Brain Neoplasms/di [Diagnosis]; *Diabetes Mellitus, Type 2/di [Diagnosis]; *Glioma/di [Diagnosis]; *Prediabetic State/di [Diagnosis]; Adult; Aged; Biomarkers; Biomarkers/bl [Blood]; Blood Glucose; Brain Neoplasms; Brain Neoplasms/bl [Blood]; Brain Neoplasms/mo [Mortality]; Brain Neoplasms/pa [Pathology]; Diabetes Mellitus, Type 2; Diabetes Mellitus, Type 2/bl [Blood]; Diabetes Mellitus, Type 2/mo [Mortality]; Diabetes Mellitus, Type 2/pa [Pathology]; Female; Glioma; Glioma/bl [Blood]; Glioma/mo [Mortality]; Glioma/pa [Pathology]; Humans; Longitudinal Studies; Male; Middle Aged; Prediabetic State; Prediabetic State/bl [Blood]; Prediabetic State/mo [Mortality]; Prediabetic State/pa [Pathology]; Prognosis; Proportional Hazards Models; Risk Factors; Time Factors; adult; aged; biological marker; blood; brain tumor; dept.pch; female; glioma; glucose blood level; human; impaired glucose tolerance; longitudinal study; male; metabolism; middle aged; mortality; non insulin dependent diabetes mellitus; pathology; peer-reviewed; prognosis; proportional hazards model; risk factor; time factor